Solar forcing of early Holocene droughts on the Yucatan peninsula - Warken, Sophie F.; Schorndorf, Nils; Stinnesbeck, Wolfgang; Hennhoefer, Dominik; Stinnesbeck, Sarah R.; Förstel, Julius; Steidle, Simon D.; Aviles Olguin, Jerónimo; Frank, Norbert (Scientific reports, 2021)
A speleothem record from the north-eastern Yucatan peninsula (Mexico) provides new insights into the tropical hydro-climate of the Americas between 11,040 and 9520 a BP on up to sub-decadal scale. Despite the complex atmospheric reorganization during the end of the last deglaciation, the dominant internal leading modes of precipitation variability during the late Holocene were also active during the time of record. While multi-decadal variations were not persistent, Mesoamerican precipitation was dominated by changes on the decadal- and centennial scale, which may be attributed to ENSO activity driven by solar forcing. Freshwater fluxes from the remnant Laurentide ice sheet into the Gulf of Mexico and the North Atlantic have additionally modulated the regional evaporation/precipitation balance. In particular, this study underlines the importance of solar activity on tropical and subtropical climate variability through forcing of the tropical Pacific, providing a plausible scenario for observed recurrent droughts on the decadal scale throughout the Holocene.
Gesehen am 09.09.2021